Effects of the interaction between dicarboxylic acid polymer and CaO on phosphorus use efficiency of cassava grown on the acidic sulfate soil in the Mekong Delta - Quyen, Nguyen Kim; Ngoc, Ngo Phuong; Thao, Pham Thi Phuong; Ly, Le Minh (Frontiers in Agronomy, 2025)
IntroductionStudies have reported that Dicarboxylic acid polymer (DCAP) -coated phosphorus fertilizer (DCAP/P) positively impacts crop growth and yield. However, studies on the effects of interaction between DCAP/P and CaO to improve the PUE of plants on acidic soils are limited. MethodsThis study aimed to (i) examine the effects of lime and DCAP on improving P uptake and cassava growth on acid sulfate soil and (ii) evaluate the effects of interaction between lime and DCAP/P on cassava PUE. The experiment was conducted in the greenhouse of the School of Agriculture, Can Tho University, from December 2022 to August 2023. The pot experiment was arranged in a completely randomized split-plot design, with factor A comprising two liming doses (0 and 4 t CaO ha-1) and factor B comprising three phosphorus (P) fertilization treatments (0P, 60P, and DCAP/60P), each with four replications. The local cassava variety ‘O Ta Bang’ was use inthe experiment.ResultOur results showed that the total P uptake (g P2O5 plant-1) at 0Pand 60P only reached 72 and 96%, respectively, compared with the total P uptake of DCAP/60P. Among the CaO-treated samples, 60P treatment increased the plant PUE to 28.6%, while DCAP/60P treatment significantly increased the PUE to 48.8%. DiscussionThe interaction between DCAP/60P and CaO synergistically enhanced PUE more efficiently than between 60P and CaO.